An improved CS imaging algorithm for GEO SAR based on cubic phase compensation in squint model - Jiang, Yicheng; Di, Xuena (2014 12th International Conference on Signal Processing (ICSP), 2014)
GEO SAR has long synthetic aperture time because of its high orbital altitude, so the conventional imaging algorithm is no longer applicable. According to the characteristics of GEO SAR imaging, in order to improve the focusing effect, in this paper, combining with the bend compensation caused by curve trajectory, the method to structure cubic phase compensation function is used in two-dimensional frequency domain to make the cubic phase compensation and the equivalent squint angle correction in squint model is used for yaw traction control. Finally a kind of improved CS imaging algorithm in squint model based on cubic phase compensation and considers of the curve trajectory is put forward. Simulation results show that the proposed algorithm can improve the focusing effect and has good imaging results.